Lateral bone density measurements in osteoarthritis of the lumbar spine. Issue 3 (March 1996) - Peacock, D J; Egger, P; Taylor, P; Cawley, M I; Cooper, C
Abstract : OBJECTIVE: To investigate whether spinal osteoarthritis (OA) is responsible for the common finding that lumbar spine bone mineral density (BMD) is greater when measured in the anteroposterior plane than when measured in the lateral plane. METHODS: We studied lateral spine radiographs from 63 women who attended a hospital outpatient department for bone density measurement and who also underwent lumbar spine radiography. Osteoarthritis was assessed using both the Kellgren and Lawrence scale and a scoring system for osteophytosis. Bone density was measured in the anteroposterior and lateral planes using a Hologic QDR-2000 instrument. RESULTS: The mean anteroposterior BMD (0.92 g/cm2) was significantly greater than the lateral BMD (0.59 g/cm2) (p < 0.01), and the difference between antero-posterior and lateral measurements was significantly associated with both increasing Kellgren and Lawrence score and osteophyte score, even after adjustment for age. CONCLUSION: These data suggest that spinal OA is a major cause of the difference between anteroposterior and lateral BMD and that lateral BMD may provide a more accurate representation of true vertebral body bone density in patients with OA of the lumbar spine.